Children With Short Stature Display Reduced ACE2 Expression in Peripheral Blood Mononuclear Cells - Tonon, Federica; Tornese, Gianluca; Giudici, Fabiola; Nicolardi, Francesca; Toffoli, Barbara; Barbi, Egidio; Fabris, Bruno; Bernardi, Stella (Frontiers in Endocrinology, 2022)
Background: The cause of short stature remains often unknown. The renin-angiotensin system contributes to growth regulation. Several groups reported that angiotensin-converting enzyme 2 (ACE2)-knockout mice weighed less than controls. Our case-control study aimed to investigate if children with short stature had reduced ACE2 expression as compared to controls, and its significance. Materials and methods: children aged between 2 and 13 years were consecutively recruited in a University Hospital pediatric tertiary care center. Cases were children with short stature defined as height SD ≤ −2 diagnosed with growth hormone deficiency (GHD) or idiopathic short stature (ISS), before any treatment. Exclusion criteria were: acute diseases, kidney disease, endocrine or autoimmune disorders, precocious puberty, genetic syndromes, SGA history. ACE and ACE2 expression were measured in peripheral blood mononuclear cells, angiotensins were measured by ELISA. Results: Children with short stature displayed significantly lower ACE2 expression, being 0.40 fold induction (0-1.77) as compared to controls, and higher ACE/ACE2, with no differences between GHD and ISS. ACE2 expression was significantly and inversely associated with the risk of short stature, OR 0.26 (0.07-0.82), and it had a moderate accuracy to predict it, with an AUC of 0.73 (0.61-0.84). The cutoff of 0.45 fold induction of ACE2 expression was the value best predicting short stature, identifying correctly 70% of the children. Conclusions: Our study confirms the association between the reduction of ACE2 expression and growth retardation. Further studies are needed to determine its diagnostic implications.